Video self-modelling as a classroom based intervention to reduce off-task behaviour in mainstream students : a thesis presented in partial requirement for the degree of Master of Educational Psychology at Massey University, Albany, New Zealand - Livermore, David (Massey University, 2012)
Video Self-Modelling (VSM) is an intervention which involves individuals observing images of themselves engaged in adaptive behaviour to increase the probability of adaptive behaviour occurring again. VSM has been used to improve academic success and/or promote positive change in a range of internalising and externalising behaviours such as mutism, social initiations, stuttering, aggressiveness, attending to task, and distractibility. Many of the current studies on the effects of VSM as a behaviour intervention have focused on students who have been referred for problem behaviour and/or been diagnosed with a disorder such as Attention Deficit Hyperactivity Disorder (ADHD), Selective Mutism, Autistic Spectrum Disorder (ASD), or Oppositional Defiant Disorder (ODD). There are few studies on the effects of VSM as a behaviour intervention for students in mainstream school who have not been referred for problem behaviour. The purpose of this research was to examine the effects of VSM on four, Year 7 students in a mainstream, intermediate school who engaged in three off-task behaviours (out of seat without permission, talking without permission, and making inappropriate noises/calling out). Prior to school each day each participant viewed themselves working on-task during literacy in an edited video clip for three weeks. The occurrence of off-task behaviour and the number of words written by participants in each 20 minute writing task was recorded during baseline, intervention, and post-intervention phases. Results indicated that students reduced in off-task behaviour and increased the number of words produced. Practical implications are discussed.
Keywords: Video self-modelling (VSM); Behaviour modification; VSM in education; Problem behaviour